Rock porosity estimation research using refraction seismic waves in Bora Village, Sigi Regency. Issue 1 (January 2021) - Sandra,; Efendi, Rustan; Astuti, Meila; Rusydi,; Badaruddin,; Iqbal,
Abstract: Rock Porosity Estimation Research Using Refraction Seismic Waves in Bora Village, Sigi Regency has been conducted. The purpose of this study was to determine the distribution of porosity of shallow subsurface rocks at geothermal locations. Data is collected on 6 different trajectories using ES-3000 to get a picture of subsurface waves. The data processing method uses Seisimager software to get a cross-section of the wave velocity and Rockwork software to get a cross-section of the porosity of subsurface rocks. The results showed different rock porosity values for each trajectory. Rock porosity values obtained at track 1 to track 6 are in the range of 27.1% to 30.5%. All trajectories are on a special porosity scale which means they have a large porosity volume as a place to store fluid.